СУҒУРТА ХИЗМАТЛАРИ БОЗОРИДА МАРКЕТИНГ ФАОЛИЯТИНИ ТАДБИҚ ЭТИШ АСОСЛАРИ - Рахимов Ойбек Бахтиѐрович (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article reveals the basics of marketing activities in the market of insurance services. Also, the role and application of marketing in the insurance market is covered in detail.